Identify and Analysis of Performance Evaluation Indicators of Iranian Goalball Coaches - Hossein Abdolmaleki; Zahrasadat Mirzazadeh; Mahboobeh Allahyari; Mahboobeh Ramezani (The Society of Aging and Physical Activity (SAPA), 2015)
Assessment of performance in the sports industry is an important issue which has attracted the attention of many researchers. One of the important human resources that have a prominent role in the success of sports organizations are coaches and especially club coaches that smallest decisions of them can affect the performance of the entire organization. The purpose of this study was to explore the most important criteria for evaluating the performance of Goalball coaches in Iran. The population consists of all coaches and head coaches and players working in Iran professional Goalball leagues. According small size of the population, sample was considered statistically equal that finally 37 coach and 110 Goalball players (total of 147) questionnaires were collected for data analysis. In this study, a researcher made questionnaire was used. The factors in performance evaluating of Goalball in perspective of coaches were behavioral factor, technical-education factor, team and individual management, experience factor and finally preservation and promotion of team, respectively. Results showed that there are significant differences between coaches and players in combination of education, experience and the management team and individual. But there was no significant difference between the views of coaches and players in the rest. The most important factor in performance evaluating of coaches was technical-education factors, researcher offer to club managers, only by the number of wins and losses of their coaches, not to choose or dismiss their coaches and use from sub-component obtained for choose or dismiss their coaches.